Evaluation of Palm Oil Mill Effluent Treatment Concomitant Phenolics Production by Aspergillus Niger IBS-103ZA - Idris, Zulkarnain Mohamed; Jamal, Parveen; Alam, Md. Zahangir (2011)
Previous results show that fermentation of palm oil mill effluent (POME) with Aspergillus niger IBS-103ZA has successfully increased the phenolic content and also antioxidant activities of the extract [1]. In this study, the potential use of Aspergillus niger IBS-103ZA to treat the effluent for removal of chemical oxygen demand (COD) and heavy metals were evaluated. The percentage of COD removal was very low. Only 24.44% of COD was removed after 120 hours of fermentation period. Aspergillus niger IBS-103ZA biomass absorbed Pb2+ ions from POME more rapidly than Zn2+ ions. Within 24 hours of fermentation period, the percentage removal of Pb2+ ions was 76.08%. The Pb2+ ions were totally removed after 72 hours of fermentation period. The removal of Zn2+ ions from POME was not as efficient as Pb2+ ions. Only 24.79% of Zn2+ ions were removed after 120 hours of fermentation period. No Cd was detected in POME during the study. Thus, treating POME via fermentation with Aspergillus niger IBS-103ZA not only increases its value added product but also reduces the pollution load in the effluent.